Chemical and microstructural controls on viscoplasticity in Carbopol hydrogel. (14th March 2018) - Shafiei, Mohammadreza; Balhoff, Matthew; Hayman, Nicholas W.
Abstract: Many engineering and natural materials, as well as earth systems, exhibit a combination of elastic-plastic and viscous behaviors, but precisely evaluating their rheology, and the micromechanics and chemical-mechanical feedbacks governing such rheology, can be a challenge. The cross-linked polymer Carbopol has long been used to explore fundamental rheological behaviors, most recently including fracturing during viscous creep in nature. Here, through rheometer experiments we establish that Carbopol 940 is, to a first order, a Herschel-Bulkley material. However, we further establish that the yield stress and viscosity are affected by chemically-sensitive micromechanical controls, namely pH and concentration of the polymer mixture. We explore these effects via the novel use of cryogenic scanning electron microscopy (SEM). Through the SEM imaging we show that there is a semi-quantitative relationship between pH, porosity at the >10-μm scale, and yield stress, a result of the ionic repulsion between polymer links at the molecular scale. We appeal to a model wherein the yield stress is a direct function of jamming expressed at the SEM scale, similar to those described in granular systems. As the pH of polymer dispersion increases, and the porosity decreases, the yield strength increases as a result of the increasingly jammed system. The initial viscosity is thus controlled by the yield stress, but after failure evolves with increasing shear rate due to characteristic unjammed flow of the material. The different controls on the yield stress versus viscous flow rates has implications for borehole engineering efforts (carbon capture and storage) employing Carbopol, and could prove instructive for modeling of natural viscoplastic deformation.